The right to choose (Khiyar) innovation for contemporary transaction in e-commerce marketplace - Windiana Lorien; Rahmad Hakim; Arif Luqman Hakim (Universitas Negeri Surabaya, 2022)
This study aims to analyze and compare the implementation of khiyar in online transactions at Shopee, Tokopedia, and Bukalapak. This type of research is a comparative study with a qualitative approach in comparing the implementation of khiyar at Shopee, Tokopedia and Bukalapak. This study uses primary data sources and secondary data sources, with data collection techniques in the form interviews and documentation. Data analysis in this study uses data analysis model of Miles, Huberman and Saldana. The results found that There are similarities transaction procedure that applies in the three marketplaces which are two types of khiyar applied, namely khiyar 'aib and khiyar ru'yah. Based on experienced transaction process carried out by sellers at Shopee, Tokopedia and Bukalapak, it was known that there are four sellers who both apply khiyar 'aib, while the application of khiyar aib was only applied by buyer at Tokopedia. On the other hand, khiyar ru'yah was not applied by buyers at Bukalapak but it was only applied by one buyer at Shopee and Tokopedia.